2021
DOI: 10.3389/fpsyg.2021.723518
|View full text |Cite
|
Sign up to set email alerts
|

“Everything Will Be All Right!” National and European Identification as Predictors of Positive Expectations for the Future During the COVID-19 Emergency

Abstract: During the first national lockdown imposed in a Western country to reduce the impact of the COVID-19 pandemic, many Italians tried to boost their spirits by hanging hand-drawn rainbows with the slogan “Everything will be all right” from their windows. To understand which processes might have nurtured their positive views about the future during the pandemic, the present study (N=846), building upon social identity research, examined the relationships among Italians’ identification with their country and with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 72 publications
(93 reference statements)
0
11
1
Order By: Relevance
“…Accordingly, it is believed that various information campaigns to be carried out in the future will create positive awareness about the vaccine fear and vaccine hesitancy status of the public. Moreover, the literature showed that identification with both membership groups, the national government and supranational entities (e.g., the European Union) can model and affect vaccine fear and vaccine hesitancy, helping to deal with the COVID-19 pandemic [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, it is believed that various information campaigns to be carried out in the future will create positive awareness about the vaccine fear and vaccine hesitancy status of the public. Moreover, the literature showed that identification with both membership groups, the national government and supranational entities (e.g., the European Union) can model and affect vaccine fear and vaccine hesitancy, helping to deal with the COVID-19 pandemic [ 82 , 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our results also illuminate the importance of European identification. Previous research has shown that European identity constitutes a protective factor that increases trust in institutions and improves expectations regarding the future [ 35 ], while reducing the wishes for stronger leadership [ 36 ]. The present study adds to this evidence by showing the role of European identification in promoting behaviors that effectively combat the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaire includes other measures that are not analyzed in the present paper (e.g., positive expectations about the future, coping strategies). Findings from the entire research project were already included in a previous publication [ 35 ], which focused on a different issue and tested different hypotheses. Two of the measures considered here (identification with Italians and identification with Europeans) were included in the publication.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study analyzed possible psychosocial antecedents that buffered or increased the wish for a strong leader during the COVID-19 crisis. First, we drew from research in the social identity framework ( Tajfel and Turner, 1979 ), which emphasized that people cope with crises more effectively if they can rely on a stronger sense of belonging and connectedness to significant groups ( Jetten et al, 2020 ; Moscatelli et al, 2021 ). Accordingly, we examined whether Italians’ increasing levels of identification with two significant entities involved in facing the pandemic – namely, their nation and the superordinate entity of the European Union (EU) – were related to a lower wish for a strong leader.…”
Section: Introductionmentioning
confidence: 99%